2022
DOI: 10.3389/fpls.2022.1000297
|View full text |Cite|
|
Sign up to set email alerts
|

Small secreted peptides encoded on the wheat (Triticum aestivum L.) genome and their potential roles in stress responses

Abstract: Small secreted peptides (SSPs) are important signals for cell-to-cell communication in plant, involved in a variety of growth and developmental processes, as well as responses to stresses. While a large number of SSPs have been identified and characterized in various plant species, little is known about SSPs in wheat, one of the most important cereal crops. In this study, 4,981 putative SSPs were identified on the wheat genome, among which 1,790 TaSSPs were grouped into 38 known SSP families. The result also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 79 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have showed that a large number of CEP genes can be induced by abiotic stresses, and some CEPs are involved in ABA signaling and plant stress responses in Arabidopsis , Setaria and Triticum (Smith et al 2020 ; Zhang et al 2021 ; Tian et al 2022 ; Taleski et al 2023 ). In this study, a total of 21 SlCEP genes (4 unannotated) were identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have showed that a large number of CEP genes can be induced by abiotic stresses, and some CEPs are involved in ABA signaling and plant stress responses in Arabidopsis , Setaria and Triticum (Smith et al 2020 ; Zhang et al 2021 ; Tian et al 2022 ; Taleski et al 2023 ). In this study, a total of 21 SlCEP genes (4 unannotated) were identified.…”
Section: Resultsmentioning
confidence: 99%
“…3 A). SSP families such as CLE, CEP, RALF and PIP, which have been reported to be involved in abiotic stress (Atkinson et al 2013 ; Takahashi et al 2018 ; Tian et al 2022 ; Zhou et al 2022 ), showed low expression levels. In the online resource for tomato transcriptome analysis (GSE151277, https://www.ncbi.nlm.nih.gov/geo/ ), the expression levels of tomato genes were examined 1, 2, 3, 4 and 5 days after drought treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several plant peptide signals have been characterized as being involved in stress responses [7,13,60]. In addition to CLE members CLE25, CLE9, and CLE14, which function as regulators of stress tolerance in Arabidopsis [37,40,41], members in the CEP family [61], RALFL family [62], Pep family [63], CAPE family [64], PIP family [65], and SCREW family [66] have been reported to be involved in plants' responses to abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Plant signaling peptide was first reported in tomato (Lycopersicon esculentum) in 1991 when systemin was identified as a hormonal peptide [2]. A large number of signaling peptides (or peptide hormones) from various plant species have been identified and characterized since then [3][4][5][6][7]. It is generally believed that plant peptide hormones are a class of mature peptide molecules with a length of fewer than 100 amino acids and special functions, and their concentrations are usually very low in plant cells [8,9].…”
Section: Introductionmentioning
confidence: 99%